Studi Kasus : Karakteristik Batuan Area Break Through Terowongan Pengelak Bendungan Ladongi - Bambang Hambar Eko Prasetyo, (ReTII, 2022)
The characteristic of mica schist rock in the diversion tunnel in the break through zone are composed of quarzite veins that have been crushed into clay-filling material and are arranged in open joints. The presence of water seepage on the roof of the tunnel is also a factor that triggers the collapse during excavation of the evasive tunnel penetration. The focus of the research is on the break through area of Sta 0+167,70 to Sta 0+176,70 of the diversion tunnel Ladongi Dam, about 9 meters long. The diversion tunnel is located in the Mekongga Formation (Pzm) with the main composition being mica schist rock. The purpose of this study was to determine the rock characteristics in the break through area using pore boring and RMR method. The result showed that the break through area is composed of two classes of rock in engineering geology, namely CL-CM and CH. The rock class is CH at the bottom and crown of the tunnel excavation, while the middle is composed by the CL-CM class and locally at the top of the tunnel. From the result of this study, it is possible to assess the characteristics of the rock material making up the break through area.